2018
DOI: 10.1016/j.jviromet.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of an anti-dengue NS1 IgG ELISA to evaluate exposure to dengue virus

Abstract: Dengue virus infection elicits immune responses to multiple viral antigens including antibodies to dengue non-structural protein 1 (NS1) which are rapidly induced and detected within days of infection. The recombinant, live, attenuated, tetravalent dengue vaccine (CYD-TDV; Sanofi Pasteur) uses the yellow fever vaccine virus as a back-bone but expresses dengue virus pre-membrane and envelop proteins. Since CYD-TDV does not express dengue NS1, we evaluated the utility of dengue NS1-specific IgG antibodies as bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 17 publications
3
43
0
3
Order By: Relevance
“…Another study using a mixed DENV1-4 NS1 IgG ELISA to determine DENV immune status among Dengvaxia recipients reported high sensitivity and specificity. However, limited numbers of other flavivirus controls (4 ZIKV and 3 WNV samples) showed positivity (40), raising concerns about its practical application in regions of endemicity where multiple flaviviruses are prevalent. With Ͼ124 control samples, including naive, pZIKV, and pWNV panels, our DENV1-4 NS1 IgG ELISA showed specificity at levels to suggest it might be a useful tool to determine DENV immune status in regions of endemicity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using a mixed DENV1-4 NS1 IgG ELISA to determine DENV immune status among Dengvaxia recipients reported high sensitivity and specificity. However, limited numbers of other flavivirus controls (4 ZIKV and 3 WNV samples) showed positivity (40), raising concerns about its practical application in regions of endemicity where multiple flaviviruses are prevalent. With Ͼ124 control samples, including naive, pZIKV, and pWNV panels, our DENV1-4 NS1 IgG ELISA showed specificity at levels to suggest it might be a useful tool to determine DENV immune status in regions of endemicity.…”
Section: Discussionmentioning
confidence: 99%
“…The Eurimmune USUV IgG ELISA is based on the viral structural proteins and these assays suffer from broad antigenic cross-reactivity of anti-flavivirus antibodies [32]. To this end the use of secreted flavivirus NS1 as an antigen alternative to virion proteins for the detection of IgM/G has proven to provide a better level of specificity [24,[33][34][35][36][37][38]. NS1 is secreted as a glycosylated oligomer in high amounts during the viremic phase and its detection is considered a marker of infection [39].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of specific antibody responses to NS1 using IgM and IgG antibody capture enzyme-linked immunosorbent assays (MAC-and GAC-ELISAs) could provide an alternative approach for the identification of infectious flaviviruses [28][29][30]. In addition, it has been reported that anti-JEV NS1 antibodies can function as serological markers of natural infection within the vaccinated population [31,32], and anti-DENV NS1 IgG ELISA can detect previous dengue exposure prior to vaccination [33]. In particular, the detection of previous exposure and quantification of the serostatus is important prior to vaccination, as flavivirus cross-reactive antibodies may contribute to the severity of secondary flavivirus infection, owing to antibody-dependent enhancement (ADE) [34].…”
Section: Discussionmentioning
confidence: 99%